Efficiency of public spending at the municipal level: evidence for the Peruvian case 2017–2023 - Lino, Carmen Nievez Quispe; Apaza, Raul Rojas; del Pilar Blanco Espezua, María (Frontiers in Political Science, 2025)
This study evaluates the determinants of public spending efficiency at the provincial level in Peru by integrating Data Envelopment Analysis (DEA) with two alternative econometric models: a bootstrapped random-effects Tobit model and a spatial Durbin model. Using panel data from 196 provinces over 7 years, DEA efficiency scores under constant returns to scale (CRS) and variable returns to scale (VRS) were estimated and analyzed to assess the impact of intergovernmental transfers, local tax revenues, and spatial interdependencies. The Tobit model accounts for the bounded nature of efficiency scores and shows that FONCOMUN transfers significantly improve both technical efficiency (VRS_TE) and scale efficiency, while canon transfers primarily enhance scale efficiency due to their infrastructure-oriented allocation but have limited effects on managerial performance. Local tax revenues positively influence technical efficiency, reflecting better expenditure management in fiscally autonomous municipalities, but they have no significant effect on scale efficiency. In contrast, the spatial Durbin model captures spatial dependencies and reveals significant negative spillover effects, indicating that higher efficiency in neighboring provinces can reduce local efficiency due to competition for resources and overlapping administrative functions. These findings contribute to the literature by providing robust empirical evidence on the interplay between fiscal transfers, managerial capacity, and spatial interdependencies, offering actionable insights for policymakers seeking to optimize local government performance and improve public service delivery.